MEASUREMENT EFFICIENCY OF PRODUCING AND MARKETING FOR THE PEANUT CROP IN DIYALA PROVINCE. - Zaidan, Ali G.; Khater, Saadoun F. (Diyala Agricultural Sciences Journal, 2013)
Peanut is consider an important economic crop in world. also consider an important industrial and oil crop, chosen Diyala governorate have been as a case study because of its importance in peanut cultivation, study aimed to measure efficiency of producing and marketing for the Peanut, The results of quantitative analysis that cost function Cube is most appropriate for relationship adopted in study according to tests of economic, statistical and standard, The results showed efficiency of producing toward 12.6 tons. estimated efficiency in production toward 67% estimated cost efficiency toward 0.73 , estimated the size production the profit short-run toward 15.33tons, estimated the net revenue on size of production actual and size of production optimization and size production the profit to reach 2440.514 ،4326.836 ، 4838.986 ID/ tons on collation, estimated the Efficiency of marketing toward 63.96%.